Rancang Bangun Game Patih Kebo Iwa Begenre Turn Based Role Playing Game Berbasis Android - Alit Rangkan Nuaja, I Wayan; Cahyawan Wiranatha, Anak Agung Ketut; Suar Wibawa, Kadek (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2022)
Game is a means of entertainment that can provide lessons for its users. This research offers a solution, namely the making of Game Patih Kebo Iwa with an android-based turn based rpg genre by telling the struggle of Kebo Iwa to become a mainstay patih of Bali until he was willing to sacrifice for the land of Bali when the devious politics carried out by Gajahmada to subdue the Balinese kingdom. The purpose of this research is to know the design of this game and measure the feasibility of the aspects of functionality and usability with ISO 9126. The game is made using the Unity application with the C# programming language. Game testing was carried out using a media questionnaire filled out by gamers. The results of this game include 20 characters, 4 main scenes, 15 maps, player movement mechanisms, battle mechanisms, menu mechanisms, item mechanisms, shop mechanisms. Testing on this game shows 100% valid results from the functionality aspect. From the usability aspect, it shows that 82% of respondents accept this game in terms of information, convenience, and ease of playing this game.